2020
DOI: 10.1002/mde.3139
|View full text |Cite
|
Sign up to set email alerts
|

Managerial style in cost asymmetry and shareholder value

Abstract: We show that CEOs' contribution to SG&A cost asymmetry is associated with lower shareholder value. CEO-related excess SG&A cost stickiness of CEOs with compensation less tied to shareholder value creation and high power drive this association.Last, we provide first evidence that cost asymmetry incorporates a harmful element to the firm and shareholders, namely CEO-related excess SG&A cost asymmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…The fifth cluster reviews sticky cost research in the manufacturing businesses including agile manufacturing, inventory control and management, and lean manufacturing (Azeez et al, 2017;Kroes & Manikas, 2018). Finally, the sixth cluster examines the occurrence of sticky costs due to leadership/manager/CEO characteristics related to optimism and overconfidence Bu et al, 2015;Ciftci & Zoubi, 2019;Hur et al, 2019;Krisnadewi & Soewarno, 2021;Lai et al, 2021;Lopatta et al, 2020;Yang, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The fifth cluster reviews sticky cost research in the manufacturing businesses including agile manufacturing, inventory control and management, and lean manufacturing (Azeez et al, 2017;Kroes & Manikas, 2018). Finally, the sixth cluster examines the occurrence of sticky costs due to leadership/manager/CEO characteristics related to optimism and overconfidence Bu et al, 2015;Ciftci & Zoubi, 2019;Hur et al, 2019;Krisnadewi & Soewarno, 2021;Lai et al, 2021;Lopatta et al, 2020;Yang, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…We use this procedure to classify firms, introductory stages, growth stage, maturity stage, shake-out, or decline in the year they join the UNGC. This method of life cycle classification is also used by Hasan (2018), Lopatta et al (2020), Meza et al (2020), andBlomkvist et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…A total of two articles were conceptual papers Guenther et al, 2014), and 24 articles did not discuss the determinants of cost stickiness but instead used them as independent variables. These articles have not been used because they discuss the effects of cost stickiness on, for example, the forecasting of earnings (Ciftci et al, 2016;Ciftci & Salama, 2018;Kaspereit & Lopatta, 2019;Lopatta et al, 2020;Lu et al, 2020;Tang et al, 2020;Weiss, 2010). Be cause our focus is the managers' behaviour, we have dropped 15 articles that discuss, for example, the effect of an auditor's choice, ac counting policies, changes in office address, CEO structure, and changes in the research sample on cost stickiness (Chae & Chung, 2015;Chae & Ryu, 2016;Chung et al, 2019;Ibrahim, 2018;Lee et al, 2019;Loy & Hartli eb, 2018;Shust & Weiss, 2014;Xue & Hong, 2016;Yang, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…As users of cost account ing information, we need to understand the causes of the asymmetry of cost behaviour, especially cost stickiness. Studies have even shown that cost stickiness (CS) affects the company's stock performance (Ciftci et al, 2016;Ciftci & Salama, 2018;Kaspereit & Lopatta, 2019;Lopatta et al, 2020;Lu et al, 2020;Tang et al, 2020;Weiss, 2010). The asymmetry of cost behaviour is due to individual management considerations in ma king decisions.…”
mentioning
confidence: 99%